APAKAH LEARNING LOSS BERPENGARUH TERHADAP KEMAMPUAN NUMERASI SISWA? - Arif Widodo; Umar Umar (JS (JURNAL SEKOLAH), 2022)
Abstract: The pandemic has the potential to cause learning loss. This study aims to determine students' numeracy skills during the pandemic. The indicator of numeracy ability in this study is the students' ability to solve basic arithmetic operations. The type of research used is survey research. Data collection using test instruments. The research subjects were 110 elementary school students. Data were analyzed using descriptive statistics. The data is presented in the form of tables and diagrams. The results showed that the number of students who could not perform basic arithmetic operations was 87%, multiplication 48%, subtraction 38%, and addition 17%. The data shows the low ability of students in the field of basic numeracy during the pandemic. Learning loss during the pandemic also has an impact on the decline in students' numeracy abilities. Keywords: numeracy abilities, learning loss, primary school  Abstrak: Pandemi berpotensi menyebabkan terjadinya learning loss. Penelitian ini bertujuan untuk mengetahui kemampuan numerasi siswa selama pandemi. Indikator kemampuan numerasi dalam penelitian ini adalah kemampuan siswa dalam menyelesaikan soal operasi hitung dasar.  Jenis penelitian yang digunakan adalah penelitian survei. Pengumpulan data menggunakan instrumen tes. Subjek penelitian sebanyak 110 siswa sekolah dasar. Data dianalisis menggunakan statistik deskriptif. Data disajikan dalam bentuk tabel dan diagram. Hasil penelitian menunjukkan bahwa jumlah siswa yang tidak dapat melakukan operasi hitung dasar pembagian sebesar 87%, perkalian 48%, pengurangan 38% dan penjumlahan 17%. Data tersebut menunjukkan rendahnya kemampuan siswa dalam bidang numerasi dasar selama pandemi. Learning loss selama pandemi juga berdampak pada menurunnya kemampuan siswa dalam bidang numerasi dasar. Kata kunci: kemampuan numerasi, learning loss, sekolah dasar,